2016
DOI: 10.1002/jbmr.2926
|View full text |Cite
|
Sign up to set email alerts
|

CCN1 Promotes VEGF Production in Osteoblasts and Induces Endothelial Progenitor Cell Angiogenesis by Inhibiting miR-126 Expression in Rheumatoid Arthritis

Abstract: Angiogenesis is the formation of new capillaries from preexisting vasculature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
77
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 71 publications
(78 citation statements)
references
References 44 publications
(59 reference statements)
0
77
0
Order By: Relevance
“…Mononuclear cells were isolated from blood components by centrifugation on Ficoll-Paque plus (Amersham Biosciences, Uppala, Sweden). EPCs were characterized and maintained using methods described in our previous reports [9,40]. …”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Mononuclear cells were isolated from blood components by centrifugation on Ficoll-Paque plus (Amersham Biosciences, Uppala, Sweden). EPCs were characterized and maintained using methods described in our previous reports [9,40]. …”
Section: Methodsmentioning
confidence: 99%
“…In vivo angiogenic activity was evaluated by CAM assay, as described in our previous reports [9,38,39]. Data were examined by microscopy and photographed using a digital camera.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Adiponectin induces ostoblast production of mediators that drive synovitis and joint destruction such as matrix metallo-proteinase-1 (MMP-1) and MMP-13, and vascular endothelial growth factor (VEGF) [44,45]. Recently, Chen et al [46] have observed that the pro-inflammatory cytokine Cysteine-rich 61 (Cyr61 or CCN1), a secreted protein from the CCN family, induces VEGF expression in osteoblasts and increases endothelial progenitor cells angiogenesis in RA. Adiponectin is also involved in RA bone remodeling by inhibiting Osx and inducing OPG expression in osteoblasts [44].…”
Section: Osteoblast Role In Ramentioning
confidence: 99%